Influence of drinking water quality on the population health in the hulyaipilskyi rural district - Hryhorenko, Luibov (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2020)
Introduction. The data presented by us is characterize priority problems in the field of drinking water supply and quality of drinking water that are relevant for many regions of Ukraine, including for Hulyaipilskyi district of the Zaporizhzhskyi region, whose population receives drinking water with deviations in some indicators from hygienic standards. Objective - to study impact of mineral composition of drinking water on the health state population in five experimental districts (Vozdvyzhenskyi, Komsomolskyi, Novozlativskyi, Uspenivskyi and Malynovskyi) of Zaporizhzhskyi region in comparison with control Hulyaipilskyi district (with the lowest levels of diseases among population). Materials and methods. Study of drinking water quality from centralized and decentralized water supply sources in Hulyaipilskyi district (102 studies in total). Indicators of general and primary morbidity among adult population in Hulyaipilskyi district were studied for the last 5-year period (280 studies in total). Indicators of general and primary morbidity among adult population in the individual hospital districts were analyzed according to the medical records (350 studies totally). Results. Deterioration of the qualitative composition of drinking water with an increased level of total mineralization during 2015–2019 was established on the territory of individual rural areas: from 1.15 to 21.82 times. A reliably high level prevalence of kidney stones and diseases of the urinary system, diseases of the circulatory system, hypertension, coronary heart disease was shown in the territory of rural districts: Komsomolskyi, Novozlatopilskyi, Uspenskyi and Malinovskyi among adult population, compared with average annual indicator in the Hulyaipilskyi rural district (p < 0.001). Conclusions. There was a tendency to increase incidence of hypertension in all rural hospital areas during 2015–2019 years. Statistically significant correlation of average strength were revealed between individual components of the mineral composition of drinking water: hardness, dry residue, total mineralization and prevalence of III, XIV classes of diseases by ICD-10 (r = 0.30, p < 0.05).